Pelestarian budaya Jawa dan identitas melalui konten TikTok Mikopedia.id - Wijayanti, Jelita Astri; Hapsari, Swita Amallia (Universitas Garut, 2026)
Abstract The development of digital technology and social media has significantly changed patterns of public communication, but it also poses challenges to the sustainability of local cultures, including regional languages. Javanese, as one of the largest regional languages in Indonesia, has begun to experience a decline in use, particularly among younger generations who tend to use Indonesian or mixed languages in digital spaces. This situation raises concerns about the sustainability of Javanese cultural identity amid the currents of globalization. On the other hand, social media platforms such as TikTok also provide new opportunities to introduce and preserve local culture through creative content that is easily accessed by the wider community. This study aims to examine how the preservation of the Javanese language and cultural identity is represented through the content of the TikTok account Mikopedia.id. This research applies the STEPPS theory proposed by Jonah Berger, which includes Social Currency, Triggers, Emotion, Public, Practical Value, and Stories. The research method used is descriptive qualitative, with data collection techniques conducted through observation of TikTok content from Mikopedia.id and interviews with the content creator as the main informant. The results show that the Mikopedia.id account consistently uses the Javanese language in its content as an effort to preserve culture. Through the presentation of everyday life content, humor, and the use of Javanese speech levels, the content is able to attract audience attention while reintroducing Javanese cultural values to younger generations in the digital era, and demonstrates the potential of social media as a new space for maintaining the sustainability of local language and cultural identity. Keywords: Cultural identity; javanese language; preservation; STEPPS theory; tiktok. Abstrak Perkembangan teknologi digital dan media sosial telah membawa perubahan dalam pola komunikasi masyarakat, namun di sisi lain juga menimbulkan tantangan terhadap keberlangsungan budaya lokal, termasuk bahasa daerah. Bahasa Jawa sebagai salah satu bahasa daerah terbesar di Indonesia mulai mengalami penurunan penggunaan, terutama di kalangan generasi muda yang lebih sering menggunakan bahasa Indonesia atau bahasa campuran dalam ruang digital. Kondisi ini menimbulkan kekhawatiran terhadap keberlangsungan identitas budaya Jawa di tengah arus globalisasi. Di sisi lain, media sosial seperti TikTok juga membuka peluang baru dalam memperkenalkan serta melestarikan budaya lokal melalui konten kreatif yang mudah diakses oleh masyarakat luas. Penelitian ini bertujuan untuk mengetahui bagaimana pelestarian bahasa dan identitas budaya Jawa ditampilkan melalui konten pada akun TikTok Mikopedia.id. Penelitian ini menggunakan teori STEPPS yang dikemukakan oleh Jonah Berger yang meliputi Social Currency, Triggers, Emotion, Public, Practical Value, dan Stories. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan teknik pengumpulan data melalui observasi terhadap konten TikTok Mikopedia.id serta wawancara dengan konten kreator sebagai informan utama. Hasil penelitian menunjukkan bahwa akun Mikopedia.id secara konsisten menggunakan bahasa Jawa dalam kontennya sebagai bentuk upaya pelestarian budaya. Melalui penyajian konten kehidupan sehari-hari, humor, serta penggunaan tingkat tutur bahasa Jawa, konten tersebut mampu menarik perhatian audiens sekaligus memperkenalkan kembali nilai-nilai budaya Jawa kepada generasi muda di era digital, serta menunjukkan potensi media sosial sebagai ruang baru dalam menjaga keberlangsungan bahasa dan identitas budaya lokal. Kata-kata kunci: Bahasa Jawa; identitas budaya; pelestarian; STEPPS; tiktok.